Improving Natural Science Learning Outcomes on Natural Events Material Through Cooperative Learning Models of Teams Games Tournament Type for Class V Elementary School Students - Marfu’ Astuti; Agustin Eka Damayanti; Alexandra Stavrianoudaki; Okpala Onyinye Peace (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: This research is an effort to improve the learning outcomes of class V students in Natural Sciences subjects with a teams games tournament type cooperative learning model. Methodology: This research is classroom action research. The subjects of this research were 21 class V students, consisting of 8 boys and 13 girls. This research was carried out in 3 cycles, each cycle consisting of four stages, namely planning, implementation, observation and reflection. The data collection methods used were interviews, observation, documentation and tests. Data was analyzed statistically using a percentage formula. Main Findings: The research results show that the Teams Games Tournament type cooperative learning model can improve learning outcomes on natural events material for class V students. Improvement from pre-cycle to cycle III. The increase from pre-cycle to cycle I was 19%, from cycle I to cycle II was 24%, from cycle II to cycle III was 23%. The number of students who completed the pre-cycle was 5 students or 24% with an average score of 47.61. The number of students who completed Cycle I was 9 students or 43% with an average score of 55.71. In cycle II there were 14 students or 67% of students completed the study with an average score of 68.09, and in cycle III there were 19 students or 90% students completed the study with an average score of 74.28. Novelty/Originality of this study: This research contributes to the development of education and can provide new information on how to overcome problems that arise in the teaching and learning process. Especially in science subjects, especially to improve student learning outcomes in class V natural events material in science subjects.